Advancing Positive Psychology In South East Asia: The Importance of Culture - Intan Hashimah Mohd Hashim (Universitas Ahmad Dahlan, 2013)
Abstract Interest in the field of positive psychology has been overwhelming. This can be observed from the number of academic conferences and journals attributed to this field. Similar patterns can be observed in Asia where more and more research are concentrating on investigating constructs deemed as important within the field of positive psychology. However, comparable to other fields within psychology, positive psychology cannot ignore the importance of culture. This is especially true in South East Asian context when culture is arguably distinct from the American/European traditions in which positive psychology was originated from. Culture is likely to play a significant role in determining how human strengths are being conceptualized and nurtured and eventually determined a person’s well-being and success as experienced within that particular society. Based on some findings from a research of adolescent’s happiness and well-being in Malaysia, this paper highlights the importance of culture in advancing positive psychology in Asia. More specifically, findings from this research demonstrated the importance of positive psychology in understanding and improving quality of life for certain groups of people in a particular society and illustrated several significant cultural and subcultural differences that can potentially enrich our understanding of positive psychological constructs. Findings also indicated the importance of culturally embedded constructs such as family relations and spiritual elements in contributing to happiness. Finally findings from this study suggested the need to unpack more general constructs such as positive relationships and meanings of life as they are contextualized within a specific culture and the call for further exploration on other constructs related to human positive attributes and strengths. Keyword: positive psychology, wellbeing, and culture